Three-dimensional scanning system based on a low-cost infrared sensor - Braun, João (2021)
Nowadays, with the availability of 3D printers, the scanners for objects are becoming increasingly present since they allow to replicate objects by 3D printing, especially for small scale sizes. However, the majority of these technologies are expensive, due to the complexity of this task. Therefore, this work presents a prototype of a low-cost 3D scanning system for small objects using a point cloud to stereolithography approach where it was already validated in simulation in previous work. This concept has a restriction that the objects must have a uniform shape, i.e, without discontinuities. The architecture is composed of two stepper motors, due to their precision, a rotating plate to allow 360 degrees scans and another rotating structure that allows the infrared distance sensor to scan the object from bottom to top (90 degrees). The pr